Hubungan Antara Gaya Kepemimpinan dengan Kinerja Nakes di Puskesmas Pagar Merbau Kabupaten Deli Serdang - Imelita Rahyuni Ritonga; Rani Ramadani; Ainun Jawahir; Dessy Nurfiani; An’nas Tasya Rahmadhani; Dewi Agustina (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to ascertain the connection between the Pagar Merbau District Health Center's performance and the leadership style used in decision-making and problem-solving. In 2024, Deli Serdang. This study is cross-sectional and observational. Fifty individuals made up the sample size. A questionnaire is used as a data gathering tool in this study the test known as chi-square is the analysis that is employed. The study room demonstrates that 25 people (50%) are involved in problem-solving using a leadership style that emphasizes involvement. There are 25 individuals (50%) involved in the Making decisions process, which is more educational in character. Bivariate analysis results show that leadership style and health worker performance Community Health Center Pagar Merbau in Regency of Deli Serdang are associated, with a p-value of 0.001 and a related category since the value is greater than 0.05. The findings of the evaluation indicate that health professionals' performance, which includes their presence, teamwork, excellence of the work, professionalism, and knowledge mastery needs to be in harmony with the educational, consultative, participative, and delegative leadership style of the Pagar Merbau Health Center's chief executive. To maximize the performance of all healthcare professionals in problem-solving, The community health center's head should adopt a leadership style That's more adaptable and flexible to different circumstances.